Authorizing illicit intimacies Filipina-GI interracial relations in the postwar Philippines - Fajardo, Stephanie (Philippine Studies: Historical and Ethnographic Viewpoints, 2017)
Intimate relations between American servicemen (GIs) and Filipina women increased visibly following the Second World War in the Philippines. As interactions became routine, women who developed close interpersonal relationships with GIs became associated with vice and loose morals. This article analyzes the multiple forces that maintained such associations, including the US military and local government's interconnected forms of intimate management and Philippine cultural productions' contradictory depictions of Filipino-American intimacies. It argues that the "bar system," which arose from businesses exploiting sexual labor, the legal system combating prostitution, and health initiatives seeking to eradicate venereal disease, effectively authorized illicit intimacies.